Research & Development : There is No Way Out - Riccardo, Corrado; Prohim, Tam; Audrey, Liwan (Konrad-Adenauer-Stiftung Cambodia, 2023)
The need for digital transformation for emerging economies are substantial, promising unprecedented paces in socioeconomic development and regional and global integration. It is of significant concern that the digital sector‘s rate of growth is surpassing that of the traditional economy on a global scale. Consequently, nations that fail to engage in digitalization efforts may find themselves at a growing disadvantage.